Advanced Applications of Micro and Nano Clay Biopolymer-Based Composites - Al-Ahmed, Amir; Inamuddin, 1980- (Materials research foundations, 2022)
Due to their characteristic properties, biodegradable nature and non-toxicity, clay-biopolymer based composites have many applications in such advanced fields as drug release, antimicrobial activities, etc.